Implementasi tradisi baliung dalam projek penguatan profil pelajar pancasila di TK Tunas Mekar Desa Cipasung Kab. Majalengka - Yunita Dwi Jayanti (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The introduction of the Baliung Tradition to early childhood is a form of strengthening the learning profile of Pancasila.  The purpose of this study was to analyze the implementation of the Baliung Tradition in the Project to Strengthen Pancasila Student Profiles at Tunas Mekar Kindergarten, Cipasung Village, Lemah Sugih District, Kab.  Majalengka.  This study uses a qualitative descriptive analysis approach, using data collection techniques namely interviews, observation and documentation.  The results of this study are introducing and implementing the implementation of Baliung or laksa, not only a special food but a traditional food that cannot be obtained every time because it is only made and served at a certain time.  The ngabaliung tradition in Cipasung Village has been around for 317 years and is still being preserved today.In Majalengka, baliung can only be enjoyed once a year in the Buku Taun tradition which is still held in several villages.  Naturally, it is quite difficult to get a baliung because of the limited place and time to make it.  Three villages in Majalengka that are still processing baliung include Cipasung Village and Borogojol Village in Lemah Sugih District and Suniabaru Village in Banjaran District.  Thus, the implementation of the Pancasila Student Profile Strengthening Project can be carried out well in Tunas Mekar Kindergarten, Cipasung Village, Lemah Sugih District, Kab.  Majalengka.